1988
DOI: 10.1056/nejm198803313181302
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Therapy on Cerebral Palsy

Abstract: Legislatively mandated programs for early intervention on behalf of handicapped infants often stipulate the inclusion of physical therapy as a major component of treatment for cerebral palsy. To evaluate the effects of physical therapy, we randomly assigned 48 infants (12 to 19 months of age) with mild to severe spastic diplegia to receive either 12 months of physical therapy (Group A) or 6 months of physical therapy preceded by 6 months of infant stimulation (Group B). The infant-stimulation program included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(48 citation statements)
references
References 16 publications
2
43
1
2
Order By: Relevance
“…In general, improvements were equivalent for children with Down syndrome and children with cerebral palsy regardless of whether they received the NDT or Developmental Skills treatment models. Consistent with findings from previous studies (Bower, Michel, Burnett, Campbell & McLellan, 2001;Harris, 1997;Palmer, 1997;Palmer, Shapiro, Wachtel et al, 1988), results from our study present a sobering picture of the benefits that infants with Down syndrome and cerebral palsy attain from participating in motor intervention. Whether children received services based upon the NDT or Developmental Skills treatment models, on average their rates of motor development did not change during intervention.…”
Section: The Effectiveness Of Contemporary Motor Intervention Servicessupporting
confidence: 91%
“…In general, improvements were equivalent for children with Down syndrome and children with cerebral palsy regardless of whether they received the NDT or Developmental Skills treatment models. Consistent with findings from previous studies (Bower, Michel, Burnett, Campbell & McLellan, 2001;Harris, 1997;Palmer, 1997;Palmer, Shapiro, Wachtel et al, 1988), results from our study present a sobering picture of the benefits that infants with Down syndrome and cerebral palsy attain from participating in motor intervention. Whether children received services based upon the NDT or Developmental Skills treatment models, on average their rates of motor development did not change during intervention.…”
Section: The Effectiveness Of Contemporary Motor Intervention Servicessupporting
confidence: 91%
“…The study indicated that the higher dosage of NDT (once a week) was associated with better motor development. The Palmer et al study (123) was also carried out in the eighties of last century. This randomized controlled trial included 48 children aged 12–19 months with bilateral spastic CP (diplegic type).…”
Section: Early Intervention In Cpmentioning
confidence: 99%
“…Only part of the study was carried out with a randomized assignment to intervention or control group, which reduced the study’s validity. Overall, only one of the four studies, which evaluated the effect of early intervention that started after the age of 3 months CA provided evidence on the effect of early intervention; the Palmer et al study (123) provided moderately strong evidence that intervention by means of an infant-stimulation program provided twice per month was associated with better motor outcome than equally frequent intervention by means of NDT.…”
Section: Early Intervention In Cpmentioning
confidence: 99%
“…In a recent, well-controlled study evaluating the effects of neurodevelopmental therapy on 12-to 19-month-old children with diagnosed spastic diplegia (Palmer et al, 1988), a number of surprising and potentially important implications for family involvement emerged. Using carefully described inclusion and exclusion criteria for their subjects, examiners randomly assigned children (stratified by level of cognitive development) to one of the following two groups in which they received either (a) 12 months of neurodevelopmental therapy (Bobath, 1967) or (b) 6 months of comprehensive infant stimulation followed by 6 months of neurodevelopmental therapy.…”
Section: Children With Cerebral Palsymentioning
confidence: 99%
“…Technically, the Palmer et al (1988) investigation did not include a no-treatment control group. It is possible, although not likely, that neurodevelopmental therapy had an adverse effect on development and that infant stimulation really did not produce unusual effects.…”
Section: Notementioning
confidence: 99%